1989
DOI: 10.1093/nar/17.15.5933
|View full text |Cite
|
Sign up to set email alerts
|

The effect of specific mutations at and around thegag-polgene junction of Moloney murine leukaemia virus

Abstract: By carrying out oligonucleotide-directed mutagenesis, in vitro, on a 3.3 kb XhoI-HindIII fragment from Moloney murine leukaemia virus Mo-MuLV proviral DNA, inserted into the phagemid pTZ19R, nine separate fragments have been prepared in which mutations have been inserted at and around the gag-pol gene junction. Using these mutant fragments Mo-MuLV proviral DNA has been reassembled and cloned into pBR322. Examination of the mutant proviral DNAs in mouse culture cells indicates that a terminator codon at the gag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…These results demonstrated that the suppression signals are not specific for UAG and that mammalian cells and cell extracts contain tRNAs capable of suppressing UGA and UAA codons which appear in a retroviral context. Similar findings have been reported by other investigators working with tobacco mosaic virus (TMV) (7), Sindbis virus (8), and MuLV (9).…”
supporting
confidence: 90%
“…These results demonstrated that the suppression signals are not specific for UAG and that mammalian cells and cell extracts contain tRNAs capable of suppressing UGA and UAA codons which appear in a retroviral context. Similar findings have been reported by other investigators working with tobacco mosaic virus (TMV) (7), Sindbis virus (8), and MuLV (9).…”
supporting
confidence: 90%
“…Alternatively, readthrough over these stops could involve mechanisms that require more extensive sequence elements than we have tested here. Recently, it has been shown that viral reproduction is inhibited by mutations which disrupt a potential stem and loop structure around the suppressible amber stop codon of Moloney murine leukaemia virus [28]. Although regions with substantial secondary structure can be identified around the leaky termination regions of CarMV, MCMV and TRV (not shown), the inclusion of these sequences in our constructs (pMCMV-Am and pTRV-Op) was not sufficient to direct detectable readthrough.…”
Section: Discussionmentioning
confidence: 77%
“…This result still holds when gag is provided in trans (13). In contrast, substitution of the UAG terminator by either of the other stop codons, UAA or UGA, surprisingly gives a similar level of read-through to that seen with UAG (15) and results in productive infection (14). As expected, glutamine is not inserted in response to the UGA codon (16) and the utilization of tRNAs other than tRNAGIn hints that some feature of the RNA in the vicinity of the stop codon is a general stimulator of stop codon read-through.…”
mentioning
confidence: 98%
“…The read-through product, the gag-pol fusion polyprotein with glutamine inserted at the stop codon (10,11), is the only source of reverse transcriptase (and other pol products), since the mRNA is organized so that ribosomes cannot directly enter at the start of the pol gene. The ratio of gag to gag-pol polyproteins may be critical, since substitution of the "leaky" UAG terminator with a CAG glutamine codon resulted in the inability to produce virus (13,14). This result still holds when gag is provided in trans (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation